PENERAPAN PEMBELAJARAN TEMATIK PADA PEMBELAJARAN SECARA DARING KELAS 5 MADRASAH IBTIDAYAH PERSATUAN UMAT ISLAM HAURKOLOT - Faidhol Anwar; Abdur Rahim (JOEL: Journal of Educational and Language Research, 2022)
The Covid-19 pandemic (coronavirus disease 2019) or the coronavirus has had a tremendous impact on society, including in the world of education. One of the impacts and changes that occur is a change in mass learning methods. That is, from face-to-face learning or Offline (outside the network) to distance learning or Online (in the network). Thematic lessons given at the elementary level are also provided online. This study aims to determine the implementation and obstacles faced in thematic learning in the 5th Grade of Madrasah Ibtidaiyah PUI Haurkolot when it is done online. The type of research used in this thesis is descriptive research with a research approach using a qualitative approach. In this study, the research subjects were students and teachers at Madrasah Ibtidaiyah PUI Haurkolot Indramayu. The samples in this study were homeroom teachers and 5th-grade students of MI PUI Haurkolot. Data was collected using observation, interview and documentation techniques. Data analysis was carried out by means of data reduction. The results showed that the application of online thematic learning for grade 5 at MI PUI Haurkolot, namely the teacher applied thematic learning to students, even though the thematic concepts provided were not very visible because the teacher provided material and fixed assignments on a per-subject system. While in the learning process, only most of the assignments and orders to work on questions are sent through the WhatsApp application media. While the obstacles faced are; limited internet quota, lack of learning media, uneven information technology capabilities, and lack of understanding of thematic learning concepts.